Amino Acids and their Derivatives in Pathogenesis and Treatment of Liver Diseases - Nefyodov I.I.; Karakosh A.J.; Alufaini M.A.; Karavay P.A.; Karavay N.L. (Journal of Hematology and Oncology Research, 2019)
A mini-review of literature data on the mechanisms of formation of the stock of free amino acids and their derivatives in liver pathology and methods for correcting metabolic imbalance
Keywords: amino acids